Diagnostic studies of the Antarctic vortex during the 1987 Airborne Antarctic Ozone Experiment - Ozone miniholes - Mckenna, D. S.; Jones, R. L.; Austin, J.; Browell, E. V.; Mccormick, M. P.; Krueger, A. J. (1989)
Localized rapid reductions in total ozone (miniholes), which were observed during the Airborne Antarctic Ozone Experiment, are studied with particular attention given to meteorological aspects. It is suggested that miniholes are forced by tropospheric weather features and that they are largely reversible distortions to the airflow around the vortex. The relationship between the miniholes and upper tropospheric and lower stratospheric synoptic-scale disturbances is studied. Trajectory calculations are presented which demonstrate the exchange of air from low latitudes with air from within the vortex, with the vortex air subsequently moving to lower latitudes.